Architect A. A. Ol (1883–1958) and the SoyuzZoloto Club - Lisitsin, Vasily (project baikal, 2023)
Construction of workers’ clubs (Houses and Palaces of Culture) was an important component of the cultural policy of the young Soviet state. Architect A. A. Ol from Leningrad designed the SoyuzZoloto Club, a facility in the constructivist style for Irkutsk, which later became the House of Culture for the V. V. Kuibyshev Plant. On the basis of archival materials, the article examines the problem of adapting a competition design to the real terrain.